Walrus history around the North Water: Human–animal relations in a long-term perspective - Gotfredsen, Anne Birgitte (Ambio, 2018)
This article highlights the relationship between walruses and humans in and around the North Water polynya in a long-term perspective. The present study draws on a combination of biological, archaeological, archaeo-zoological, historical, and ethnographic sources covering the period from the 8th century ad to the late 20th century. The study demonstrates that the walrus was an important resource of meat, blubber, and other products throughout all the studied periods, if always supplemented by other kinds of game. It is suggested that walrus distribution and behaviour, as well as hunting strategies and technologies historically constituted a powerful component not only in forming human action and social life in the region but also in serving as an imaginative resource. It is further argued that the walrus and the walrus hunt still play a significant role in the present community living on the edge of the North Water, even if the hunt is increasingly circumscribed due to changing ice conditions.